2021
DOI: 10.1001/jamaoncol.2021.3441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cisplatin and Gemcitabine With or Without Berzosertib in Patients With Advanced Urothelial Carcinoma

Abstract: IMPORTANCE Preclinical studies suggest that inhibition of single-stranded DNA repair by ataxia telangiectasia and Rad3 (ATR) may enhance the cytotoxicity of cisplatin, gemcitabine, and other chemotherapeutic agents. Cisplatin with gemcitabine remains the standard up-front therapy for treatment in patients with metastatic urothelial cancer.OBJECTIVE To determine whether the use of the selective ATR inhibitor, berzosertib, could augment the activity of cisplatin with gemcitabine. DESIGN, SETTING, AND PARTICIPANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In a phase 2 trial for urothelial carcinoma therapy, berzosertib was added to gemcitabine and cisplatin as first-line treatment and compared with chemotherapy alone; PFS was not significantly different between the berzosertib group vs. chemotherapy alone (8.0 months for both arms), but overall survival (OS) was shorter in the berzosertib group (14.4 months vs. 19.8 months). The combination arm also had higher rates of serious adverse events, which were mostly related to myelosuppression [56]. Although the results of ongoing studies are anticipated, these phase 2 trial results imply that combination strategies should be optimized for the selection of partner drugs and target patients (Table 1).…”
Section: Atr Inhibitorsmentioning
confidence: 99%
“…In a phase 2 trial for urothelial carcinoma therapy, berzosertib was added to gemcitabine and cisplatin as first-line treatment and compared with chemotherapy alone; PFS was not significantly different between the berzosertib group vs. chemotherapy alone (8.0 months for both arms), but overall survival (OS) was shorter in the berzosertib group (14.4 months vs. 19.8 months). The combination arm also had higher rates of serious adverse events, which were mostly related to myelosuppression [56]. Although the results of ongoing studies are anticipated, these phase 2 trial results imply that combination strategies should be optimized for the selection of partner drugs and target patients (Table 1).…”
Section: Atr Inhibitorsmentioning
confidence: 99%
“…In phase I trials testing ATR inhibitors berzosertib and ceralasertib with chemotherapy, hematological AEs (neutropenia, anemia and thrombocytopenia), fatigue and emesis were the most common toxicities [ 22 , 96 , 97 , 98 ]. Two randomized phase II studies confirmed that the addition of berzosertib to gemcitabine in ovarian cancer patients and to cisplatin/gemcitabine in urothelial cancer patients increased the incidence and severity of hematological toxicities and the rate of nausea and vomiting [ 21 , 87 ].…”
Section: Combination Regimensmentioning
confidence: 99%
“…Among patients with lenvatinib, 7% were noted to develop cardiac dysfunction, with 2% noting grade 3 or greater. In addition to multi-kinase inhibitors, berzosertib, an inhibitor of ataxia telangiectasia and Rad3-related (ATR) protein, was evaluated in addition to chemotherapy in patients with metastatic UC who had not yet received chemotherapy for metastatic disease [ 169 ]. Unfortunately, there was no improvement in progression-free survival.…”
Section: Emerging Therapeutic Targets and Future Directionsmentioning
confidence: 99%